Pengaruh Prosedur Pembayaran Pajak, Sanksi Pajak, Kesadaran Pajak Terhadap Kepatuhan Pajak Kendaraan Bermotor Di Samsat Kabupaten Sidoarjo - Muhammad Fariz Arfiansyah; Sjarief Hidajat (Journal of Economic, Bussines and Accounting (COSTING), 2022)
State revenue in the role of taxpayers is very large. In order for taxpayers to comply with laws and regulations, taxpayers are required to comply so that state revenues can increase. However, state revenues are also increasing and the number of taxpayers may not increase because of the arrears in payment of vehicle taxes that do not pay taxes. The purpose of this study was to examine the effect of tax payment procedures, tax sanctions, and taxpayer awareness on motor vehicle taxpayer compliance. The population in this study are all motorized vehicle taxpayers registered at the Sidoarjo Regency Samsat Office. in this study using quantitative methods. The analysis used in this research is partial least square (PLS). Based on the results of this study, it was concluded that the tax payment procedure had a negative and insignificant effect on motor vehicle taxpayer compliance. Tax sanctions and taxpayer awareness have a positive and significant impact on motor vehicle taxpayer compliance. Keywords: Procedure, sanctions, awareness, compliance